J-shaped association of neutrophil-to-lymphocyte ratio with all-cause mortality and linear association with cardiovascular mortality in stroke survivors - Chen, Yiqiao; Lv, Tian; Lin, Wanyi; Meng, Tianjiao; Sui, Yi; Chen, Shiqin (Frontiers in Neurology, 2025)
BackgroundThe correlation between systemic inflammation and stroke has been well-established. Notably, the neutrophil-to-lymphocyte ratio (NLR) has been linked to poor outcomes and increased short-term mortality in acute ischemic stroke (AIS). This study aims to explore the association between NLR and long-term mortality among stroke survivors.MethodsThis study analyzed data from 1,229 stroke survivors enrolled in the National Health and Nutrition Examination Survey (NHANES) from 2001 to 2018. The participants were categorized according to quartiles of NLR level. Multivariate Cox regression and restricted cubic splines (RCS) were applied to evaluate the relationship between NLR and all-cause and cardiovascular disease (CVD) mortality.ResultsOver a median follow-up of 6.41 years, 485 deaths were recorded. After multivariate adjustment, individuals in the highest NLR quartile (Q4) demonstrated significantly higher risks of all-cause mortality (hazard ratio [HR] = 1.58, 95% confidence interval [CI]: 1.06–2.34) and CVD mortality (HR = 1.90, 95% CI: 1.07–3.37) compared to those in the lowest quartile (Q1). RCS analysis revealed a J-shaped relationship between NLR and all-cause mortality and a linear relationship with CVD mortality.ConclusionThese findings suggest a J-shaped association between NLR and all-cause mortality, along with a linear relationship between NLR and CVD mortality in stroke survivors.